(3GdfXGe GdbGfhfi dYbhO EfTGAGJ GdHfjI GdCSGSjI Yf WQjb GdJehjd GdNGU (B/ s - (3EjgGH GdSjO jhSa YHOGddg s; (3eMeO HgLJ YHOGddg bGjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3JMJhi GdQSGdI Ydi ebOeI Ke HGH JegjOi jMhi JMOjOG dehVhY GdHMK h HjGf CgejJg h JYQjag h GdaQb Hjfg h Hjf GdfXe GdeTGHgI Ke Je JbSje GdQSGdI Edi KdGKI CHhGH h Je JNUjU GdHGH GdChd dOQGSI GdWHjYI GdbGfhfjI dfXGe GdHhJ(B: (3h GdbhGYO GdbGfhfjI GdJi JMce fXGe GdHhJ ChdG h GdJcjja GdbGfhfi dfXGe GdHhJ hGdBQGA GdbGfhfjI GdJi bjdJ ai gPG GdCeQ(B. (3KGfjG h GdbGfhf GdhGLH GdJWHjb h GdENJUGU GdbVGFi HfXQ GdefGRYGJ Yf Jdc GdWGFaI ef GdeTQhYGJ(B. (3KGdKG h JfGhdfG ai GdHGH GdKGfi Gdgjcd GdJfXjei ddeTQhY h eQGMd JfajP h Jehjd GdeTQhY h GdCWQGa GdQFjSjI dg h GdeQGMd GdRefjI GdJi jeQ HgG GdeTQhY h GdEJaGbjGJ GddGReI dJehjd GdeTQhY s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2013s
(3HHdjhLQGajG(B: (3UaMGJ (B496-538s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdJehjd GdNGUs; (3GdfXGe GdbGfhfi s; (3YbhO EfTGAGJ GdHfjI GdCSGSjI s; Boot (3fXGes; Boot (3GdJcjja GdbGfhfj dfXGe s; Boot (3GdbGfhf GdhGLH GdJWHjb Ydi GdeTQhYGJ GdebGeI HfXGe Gd s; (3YbO GdebGhdI hYbO GdJTZjd hGdUjGfI s; (3GdeNGWQ GdJj jJYQV dgG eTQhY GdHhJ s; Boot(3GfJgGA GdeTQhY GdebGe HfXGe Gd s; Boot(3JShjI GdefGRYGJ GdebGeI HfXGe Gd s; Boot(3YjhH GdeTQhYGJ GdebGeI HfXGe Gd s; (3QCS GdeGd GdeTGQc s; (3TQcI GdeTQhY s; (3GdHfGA hGdJedc hfbd GdedcjI s; (3eQGMd JfajP GdeTQhY s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs